2004
DOI: 10.1007/s00259-004-1624-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metaiodobenzylguanidine activity can predict the long-term efficacy of angiotensin-converting enzyme inhibitors and/or beta-adrenoceptor blockers in patients with heart failure

Abstract: The reduction in mortality risk achieved by using ACE inhibitors and/or beta-blockers is associated with the severity of impairment of cardiac MIBG uptake. Cardiac MIBG activity can consequently be of long-term prognostic value in predicting the effectiveness of such treatment in patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 19 publications
0
36
0
2
Order By: Relevance
“…In a heterogeneous population of patients with heart failure, the most important determinant of cardiac uptake of 123 I-MIBG is the degree of impairment of the norepinephrine transporter function in presynaptic adrenergic neurons [2][3][4][5][6][7][8][9][10]. As such, considerable variation in late H/M ratio would be expected between patients with otherwise similar clinical presentations (NYHA class, LVEF, etc).…”
Section: Acquisition Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In a heterogeneous population of patients with heart failure, the most important determinant of cardiac uptake of 123 I-MIBG is the degree of impairment of the norepinephrine transporter function in presynaptic adrenergic neurons [2][3][4][5][6][7][8][9][10]. As such, considerable variation in late H/M ratio would be expected between patients with otherwise similar clinical presentations (NYHA class, LVEF, etc).…”
Section: Acquisition Parametersmentioning
confidence: 99%
“…In the past two decades, a large number of investigators have demonstrated decreased myocardial 123 I-MIBG uptake in patients with chronic heart failure (CHF) and have shown that those with the lowest uptake tend to have the poorest prognosis [2][3][4][5][6][7][8][9][10][11][12]. There have also been findings suggesting that abnormalities of myocardial 123 I-MIBG uptake may be predictive of increased risk of ventricular arrhythmia and sudden cardiac death [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…-MIBG values have been demonstrated by numerous studies to have prognostic values in congestive heart failure patients [7,10,17]. Although some study were conducted by ME collimator, many hospitals now continue to use low-energy collimators, and most of the previous data were accumulated by using low-energy collimators.…”
Section: Imentioning
confidence: 99%
“…Parameters obtained with late MIBG scintigraphy images such as heart/mediastinum (H/M) ratio and washout rate can be used as indicators for sympathetic activity. Patients with the lowest uptake of MIBG have the poorest prognosis [10,17]. Normal value of H/M differs in each institution [3].…”
mentioning
confidence: 99%
“…17 In heart failure, variations in cardiac 123 I-mIBG uptake and washout correlate with the risk of future adverse cardiac events 19 and therapeutic interventions in heart failure patients have been shown to lead to increases in uptake. [20][21][22] These findings suggest that 123 I-mIBG scintigraphy can reflect dynamic changes in adrenergic function in the heart.…”
mentioning
confidence: 99%